Henry Fielding at Work - Bertelsen, L. author. aut Link
240 p.
Keywords: As a writer, businessman and magistrate, Henry Fielding was in a singular position to textualize eighteenth-century English cultural conditions and materially to author the text of his society. Not only did he extol employment, he co-owned an employment agency. Not only did he commit fictional criminals to paper, he committed actual criminals to prison. And he could and did commit actual criminals to prison and paper simultaneously. Henry Fielding at Work examines the intersections of Fielding's practice as magistrate, businessman, and writer, and explores the ways Fielding's experience in those capacities affected the conception, form and articulation of his final literary works.